Comparative characteristic of concentration units relating to reference materials for gas chromatography analysis of hydrocarbon samples - S. A. Arystanbekova; A. B. Volynskii (Стандартные образцы)
Application of a method of absolute calibration relating to gas chromatography analysis of liquid hydrocarbon samples is considered. It is shown for this task that both from theoretical, and practical points of view the optimum concentration unit is mass (not molar) fraction. Information on average molar mass of the analyzed sample is necessary for the determination of analytes in liquid hydrocarbon samples in terms of mole fraction. Meanwhile, the normative documents of rather high rank (ASTM, ISO, GOST, GOST R) concerning methods of the determination of average molar weight of samples of such a kind are absent.